1990
DOI: 10.1111/j.1432-1033.1990.tb15517.x
|View full text |Cite
|
Sign up to set email alerts
|

On the domain construction of the multienzyme gramicidin S synthetase 2

Abstract: The multienzyme gramicidin S synthetase 2, composed of one polypeptide chain, was treated with trypsin and chymotrypsin to give fragments retaining partial enzyme activities. Previously, a tryptic fragment of this multi‐enzyme has been identified as a structural and functional domain. In this study two more fragments, activating Leu and Val, respectively, are shown to represent domains. Careful inspection of the data on limited proteolysis, from this study as well as from previous work, suggests that domains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…More reliable evidence can be obtained from limited proteolysis data, as this method is generally used to prepare stable domains. Tryptic digestion of gramicidin S synthetase 2, a 512 kDa multienzyme integrating 4 modules, led to amino acidactivating domains of I 10-115 kDa [35][36][37]. The Pro-activating domain has been analysed in detail, subcloned, and can be concluded to be truncated before the J-motif [38].…”
Section: Discussionmentioning
confidence: 99%
“…More reliable evidence can be obtained from limited proteolysis data, as this method is generally used to prepare stable domains. Tryptic digestion of gramicidin S synthetase 2, a 512 kDa multienzyme integrating 4 modules, led to amino acidactivating domains of I 10-115 kDa [35][36][37]. The Pro-activating domain has been analysed in detail, subcloned, and can be concluded to be truncated before the J-motif [38].…”
Section: Discussionmentioning
confidence: 99%
“…Protein chemical studies and the recent progress in cloning and sequencing of genes encoding peptide synthetases of bacterial and fungal origin provide valuable insights into the molecular architecture of these enzymes. A modular structure for these multienzyme complexes has emerged, in which the substrate activating/modifying units are aligned in a sequence that is colinear with the amino acid sequence of the assembled peptide. , These units have been designated as modules according to a definition originally applied by L. Katz and co-workers to the arrangement of genes encoding type I polyketide synthases . On the basis of comparison of DNA sequences encoding several peptide synthetases and recent studies on heterologous expression of DNA fragments , that encode proteins that activate individual amino acids, modules were defined as semiautonomous units within peptide synthetases that carry all information needed for recognition, activation, and modification of one substrate. This means that the number of modules and their order within a peptide synthetase define the sequence and the length of the synthesized peptide (Figure A, B).…”
Section: B Template-directed Peptide Synthesismentioning
confidence: 99%
“…While the A domain of peptide synthetases is an integrated part of a multifunctional enzyme, the homologous acyl-CoA synthases are distinct proteins. , Following the idea of the modular architecture of peptide synthetases, the question arose whether such a single A domain could function independently from the adjacent domains. The first insights were obtained through biochemical characterization of proteolytic and gene encoded fragments, expressed in E. coli , of the multimodular gramicidin S and tyrocidine synthetases, which exhibited activation of one specific amino acid residue only. , , The catalytic independence of the integrated A domain itself was demonstrated for the first time by deletion studies on the starter synthetases GrsA and TycA (Figure ). , The A domains, located in the N-terminal region, were proven to catalyze amino acid activation (Figure ) with the same specificity as the wild-type enzymes. Very recently, it has also been shown that internal A domains of the multimodular enzymes TycB and TycC can be expressed in E. coli as soluble, functional proteins …”
Section: The a Domains Are Enzymatically And Structurally Independentmentioning
confidence: 99%
“…PIE is then thought to dock onto the C-terminal ACP domain of R A P S , for the transfer of the polyketide chain to the amino group of pipecolate (3), where cyclisation takes place (4). The domain structure shown fur PIE is inferred from the sequence analysis reported here and analyses of the protein structure of peptide synthetases [9,[52][53][54] of the macrolide polyketide synthases, for example the multienzyines for the biosynthesis of erythromycin [3], avermectin 1201, and oleandomycin [45]. However, neither PIE nor the rapamycin polyketide synthase contain a thioesterase motif, nor is there an activity with similarities to discrete thioesterase enzymes in the rup cluster.…”
Section: Resultsmentioning
confidence: 90%